Expression pattern of microRNAs related with response to trastuzumab in breast cancer. Issue 9 (15th February 2019) - Yang, Fan; Fu, Ziyi; Yang, Mengzhu; Sun, Chunxiao; Li, Yongfei; Chu, Jiahui; Zhang, Yanhong; Li, Wei; Huang, Xiang; Li, Jun; Wu, Hao; Ding, Xiaorong; et al.
Abstract: Background: Although an immense effort has been made to develop a novel biomarker for response to trastuzumab, no reliable biomarkers are available to guide management, expect for HER2. The aim of this study was to examine the relationship between microRNA (miRNA) expression and resistance to trastuzumab. Methods: Differentially expressed miRNAs between trastuzumab‐resistant and trastuzumab‐sensitive cell lines were analyzed using microarrays. We performed Gene Ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses to determine the functions of differentially expressed miRNA and their targeted genes. Furthermore, the protein–protein interactions (PPI) network was analyzed. Serum samples were collected from patients with HER2‐positive breast cancer who were treated with trastuzumab. We validated the miRNAs expression levels by quantitative reverse‐transcription polymerase chain reaction (qRT‐PCR) in these serums. Receiver operating characteristic (ROC) curve analysis was performed to evaluate the predictive performance of the miRNA. Results: Using miRNA microarrays, 151 miRNAs that significant differentially expressed between the trastuzumab‐resistant and sensitive cells were identified, including 46 upregulated and 105 downregulated miRNAs. Results of real‐time PCR confirmed seven miRNAs in cell lines. PI3K‐Akt signaling pathway was involved in regulating biological function according to KEGG analysis. Compared with the serums of trastuzumab‐sensitive patients, three miRNAs, namely miR‐200b, miR‐135b, and miR‐29a, were identified to be upregulated, and miR‐224 was downregulated in the trastuzumab‐resistant serums. ROC analysis showed that four miRNAs were correlated with trastuzumab resistance. Furthermore, three subnetwork modules of PPI network were obtained. Conclusion: The results indicated that miRNAs were reliable predictive biomarkers for response to trastuzumab. Abstract : The aim of this study was to examine the relationship between a panel of microRNAs (miRNAs) expression and resistance to trastuzumab. The miRNAs in the blood may be a new biomark of trastuzumab efficacy.